2021
DOI: 10.1016/j.lfs.2020.118676
|View full text |Cite
|
Sign up to set email alerts
|

Is highly expressed ACE 2 in pregnant women “a curse” in times of COVID-19 pandemic?

Abstract: Angiotensin-converting enzyme 2 (ACE 2) is a membrane-bound enzyme that cleaves angiotensin II (Ang II) into angiotensin (1–7). It also serves as an important binding site for SARS-CoV-2, thereby, facilitating viral entry into target host cells. ACE 2 is abundantly present in the intestine, kidney, heart, lungs, and fetal tissues. Fetal ACE 2 is involved in myocardium growth, lungs and brain development. ACE 2 is highly expressed in pregnant women to compensate preeclampsia by modulating angiotensin (1–7) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 92 publications
1
37
1
2
Order By: Relevance
“…The viral agent responsible for coronavirus disease 2019 (COVID‐19), SARS‐CoV‐2 enters host cells by interacting with the angiotensin‐converting‐enzyme receptor, the levels of which are increased in the pregnant uterus and placenta, making the latter a potential target for the infection 9,10 . This assumption has been subsequently strengthened by the reported increased prevalence of signs of decidual arteriopathy in pregnant women with SARS‐CoV‐2 infection, suggesting a potential connection between infection and impaired placental function 11‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…The viral agent responsible for coronavirus disease 2019 (COVID‐19), SARS‐CoV‐2 enters host cells by interacting with the angiotensin‐converting‐enzyme receptor, the levels of which are increased in the pregnant uterus and placenta, making the latter a potential target for the infection 9,10 . This assumption has been subsequently strengthened by the reported increased prevalence of signs of decidual arteriopathy in pregnant women with SARS‐CoV‐2 infection, suggesting a potential connection between infection and impaired placental function 11‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…In pregnant women, a 2-fold increase in the expression of ACE2 receptors is observed as in different organs, including the placenta, kidneys, and gravid uterus, compared with the non-pregnant women [ 65 ]. This might also enhance the risk of infection and the severity of the SARS-CoV-2 infection in pregnant women [ 66 ]. However, further studies are required to elucidate this.…”
Section: Pregnancy and Severity Of Covid-19: Pathophysiologymentioning
confidence: 99%
“…The authors concluded that the human placenta is capable of being infected, although the polarized expression of ACE-2 towards the fetal compartment and the scarce expression of TMPRSS2 in trophoblast, remote from maternal blood, may justify the rarity of vertical transmission of COVID-19 [34] . ACE-2 is abundantly present in the heart, lungs, intestine, kidneys, and fetal tissues [35] . In live fetuses, ACE-2 receptors are involved in myocardium growth, lung and brain development [35] .…”
Section: Placental and Fetal Expression Of Ace-2 And Ang-(1-7)mentioning
confidence: 99%